Progressive Collapse Analysis of Structures : Numerical Codes and Applications - Isobe, Daigoro, author 649977; ScienceDirect (Online service) 7722 (Oxford : Butterworth-Heinemann, 2018)
Provides a new method for analysing collapse behaviours of buildings under various scenarios, such as impact, fire, blast demolition, earthquake, and tsunami. The analysis of the vulnerability of buildings against progressive collapse is a challenging task. Progressive Collapse of Structures: Numerical Codes and Applications provides a variety of numerical analysis tools and methods which allow engineers to simulate structural collapse behavior during all stages of the process.